P-028 Safety and outcome of mechanical thrombectomy in medium and distal vessel occlusions for patients with NIH stroke scale score of ≤ 6. (23rd July 2022) - Kuhn, A; Nedelcu, S; Henninger, N; Singh, J; Massari, F; Puri, A
Abstract : Introduction/Purpose: Mechanical thrombectomy (MT) has proven superior to medical management in patients with large vessel occlusions based on evidence brought forward by 5 landmark trials back in 2015. Nevertheless, the efficacy and safety of MT for patients presenting with medium and distal vessel occlusions as well as a low NIHSS is unknown. We here report our experience with MT versus medical management for patients presenting with medium/distal vessel occlusions and an NIHSS score of ≤6. Materials and Methods: We retrospectively reviewed our Comprehensive Stroke Center database and identified all patients admitted for acute ischemic stroke with NIHSS score of ≤6 between January 2018 and December 2021. We then selected the patients who had either a medium or distal vessel occlusion (M2 through M4, A2 through A4 and P2 through P4 occlusions). The patients were further divided into 2 groups, a medical management arm and MT arm. Patient characteristics, procedural data, and clinical outcome information was collected. Results: We identified 64 patients who presented with acute ischemic stroke secondary to a medium or distal vessel occlusion. Of those 37 patients were medically treated (20 males) and 27 (18 males) underwent MT. Patient age ranged from 58 to 79 years, with a mean age of 67. Middle cerebral artery occlusions in the M2 through M4 segments were seen in 48 patients, anterior cerebral artery occlusions in the A2 through A3 segments were seen in 4 patients and posterior cerebral artery occlusions involving the P2 segment were seen in 12 patients. Eleven patients received tPA. Seven patients in each group showed hemorrhage on cross-sectional imaging at 36 hours. Mean NIHSS on the day of presentation was 4 in the medical treatment group and 5 in the thrombectomy patients. Mean change in NIHSS points from day of presentation to day 1 post initiation of medical management/post-procedure was 2 points in the MT group versus 0 points in the medical management group (p=0.013). Using a multiple linear regression model, mechanical thrombectomy was independently associated with the NIHSS-shift from day 0 to 1 (Coefficient 1.133 95%-CI 0.104 to 2.162, p=0.031). Mean NIHSS at discharge was 1 in the thrombectomy group versus 2 in the medical management arm. Neurological outcome at 3 months showed mRS of 0 to 2 in 17 MT patients and 28 medical management patients. A total of 5 patients died. Conclusion: MT of medium and distal vessel occlusions in patients with low NIHSS appears feasible and safe. NIHSS score alone should not be the deciding factor on offering MT or not. An individualized decision-making approach aimed towards maximizing the patient's outcome should be the goal. Disclosures: A. Kuhn: None. S. Nedelcu: None. N. Henninger: 1; C; Funding from the CDMRP/DoD. J. Singh: None. F. Massari: None. A. Puri: 1; C; NIH, Microvention, Cerenovus, Medtronic Neurovascular and Stryker Neurovascular, . 2; C; Consultant for Medtronic Neurovascular, Stryker NeurovascularBalt, Q'Apel Medical, Cerenovus, Microvention, Imperative Care, Agile, Merit, CereVasc and Arsenal Medical. 4; C; InNeuroCo, Agile, Perfuze, Galaxy and NTI.